DIGRESSIVE ASPECTS OF RHETORICITY: THE CASE OF SCIPIO - Артеменко, Я. І.; Попова, Н. В. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2016)
The article is devoted to research of digressive aspects of rhetoric as an inter-subjective phenomenon. Rhetoric, which reveals itself as a special communication strategy, appears a practice of existential positioning as well. Digression is interpreted in relation to issues of authenticity and presence. Digression is seen in not just a technique function, which person uses to «beat» an opponent applying temporal and semantic «retention», «step-away» or «hanging». It is necessary to consider this more broadly – as a discontinuous process of existentialself-unfolding in rhetorical dialogue, exchange of communicative roles and play with meanings and limits of rhetorical capabilities. Digression is interpreted as a kind of movement of mediated presence that shows itself even through «anti-communicative» acts of rhetorical games.